ISLAMIC FINANCIAL BEHAVIOUR AS A DRIVER IN SHAPING HOUSEHOLD FINANCIAL WELL-BEING - Rizky Firmansyah; Dediek Tri Kurniawan; Vianca Annabel Rasiady (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
This study examines how Islamic financial behaviour moderates the effects of religiosity, Islamic financial literacy, and financial stress on financial well-being. Data from 247 respondents were collected and analyzed using SEM-PLS. It was found that Islamic financial literacy improves Islamic financial behaviour; however, it had no significant effect on financial well-being. The impact of religiosity is felt on Islamic financial behaviour and not on financial well-being. Financial stress is considered detrimental to financial well-being, whereas Islamic financial behaviour is negligible. Islamic financial behaviour is positively associated with financial well-being. Hence, there is a need to develop Islamic financial literacy and religiosity to positively influence Islamic financial behaviour and increase the financial well-being of Muslim households in Indonesia